2012
DOI: 10.1021/jp304460z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for the Atomic Layer Deposition of Copper Using Diethylzinc as the Reducing Agent: A Density Functional Theory Study Using Gas-Phase Molecules as a Model

Abstract: Access to the full text of the published version may require a subscription. intermediate, as otherwise it will lead to a stable copper molecule rather than copper metal. Volatile ZnL 2 will favor the ALD reaction as it will carry the reaction forward. Rights

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 35 publications
(65 reference statements)
1
48
0
Order By: Relevance
“…11 The growth mechanism of this process has been investigated using density functional theory (DFT) in a gas-phase model and it is predicted that the surface is probably covered with a Cu(I) intermediates. 12 Later, a thin film of very pure Cu has been deposited using a three-step ALD process which entails the sequential reactions of Cu(dmap) 2 , formic acid and hydrazine (N 2 H 4 ) at 120 °C. 6 Recently, low temperature Cu ALD has also been demonstrated using a two-step process of Cu(dmap) 2 and borane dimethylamine [BH 3 (NHMe 2 )]…”
Section: Introductionmentioning
confidence: 99%
“…11 The growth mechanism of this process has been investigated using density functional theory (DFT) in a gas-phase model and it is predicted that the surface is probably covered with a Cu(I) intermediates. 12 Later, a thin film of very pure Cu has been deposited using a three-step ALD process which entails the sequential reactions of Cu(dmap) 2 , formic acid and hydrazine (N 2 H 4 ) at 120 °C. 6 Recently, low temperature Cu ALD has also been demonstrated using a two-step process of Cu(dmap) 2 and borane dimethylamine [BH 3 (NHMe 2 )]…”
Section: Introductionmentioning
confidence: 99%
“…Careful thermal decomposition studies showed metal formation by the oxidation of a ligand through β-hydrogen abstraction, coupled with reductive elimination to produce one equivalent of the parent ligand ( Figure 6). It should be noted that the mechanism given in Figure 6 incorporates the chemisorption modeled at the Tyndall Institute, 12 and so is our reinterpretation of the (similar) original mechanism. In this model, the simple chemisorption of a variety of copper(II) precursors (CuX 2 ) was shown to undergo a ligand shift of one ligand to a growing copper surface while the chemisorbed species maintained its second ligand:…”
Section: Aminoalkoxidesmentioning
confidence: 80%
“…In both cases where diethyl zinc was used, reductive elimination of butane from diethyl zinc is the likely contributor to the metallic impurity, as discussed at length in a computational model from Tyndall. 12 It should be noted that the computational study modeled all species as gas phase molecules, while this review uses surface species notation (for consistency with subsequent chemical equations and schemes). In general, the elimination of ZnX 2 where X is an anionic ligand, is more likely when ZnX 2 is a more volatile species, and this was modeled in two steps in this paper ( Figure 3).…”
Section: Diethyl Zincmentioning
confidence: 99%
See 1 more Smart Citation
“…The state of the art to 2012 is summarized in ref 62. Since then, our most recent atomic-scale simulations have revealed new details of the mechanism of oxide ALD [43], have accounted for the stoichiometry of ternary oxides [63], have assessed precursor ligands for alkaline earth metal oxides [64] and for copper metal [65] and have developed kinetic Monte Carlo models of film growth [66].…”
Section: Ald Development and Understandingmentioning
confidence: 99%